Aplikasi Monitoring Energi SHS Off-Grid Menggunakan Lora - Satrio Yudho (Sekolah Tinggi Teknik PLN, 2021)
The manner of efficiency and effective of power usage is the main objective in electricity consumption, one major steps to control the usage is by providing a monitoring to aim the power usage data and process it to information needed. Internet of Things benefit in power and electricity has involved sensors to work as data reader continuously. LoRa or well known as Long Range radio communication system work with chirp spread spectrum which work from 920 to 923 Mhz in Indonesia. This paper presents implementation of LoRa system to support the prototype of energy monitoring in Solar Home System off-grid